Tổng hợp và nghiên cứu cấu trúc phức chất Ni(II) phenylen-1,2 - điamin benzamidin - Yến, Nguyễn Thị Bảo; Hải, Nguyễn Minh; Huy, Nguyễn Hùng (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: